2016
DOI: 10.1111/bph.13531
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of nitric oxide with α2‐adrenoceptors within the locus coeruleus underlie the facilitation of inhibitory avoidance memory by agmatine

Abstract: BACKGROUND AND PURPOSEAgmatine, a putative neurotransmitter, plays a vital role in learning and memory. Although it is considered an endogenous ligand of imidazoline receptors, agmatine exhibits high affinity for α-adrenoceptors, NOS and NMDA receptors. These substrates within the locus coeruleus (LC) are critically involved in learning and memory processes. EXPERIMENTAL APPROACHThe hippocampus and LC of male Wistar rat were stereotaxically cannulated for injection. Effects of agmatine, given i.p. or intra-LC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Similarly, according to Fan et al obtained results of an animal study, corticosterone and stress increase the expression of adrenaline-producing enzymes in LC, boost the function of the basolateral amygdala (BLA) and development of avoidance behavior [15]. Also, Shelkar et al have been reported that interaction between LC-NE and NO facilitates the expression of avoidance behavior [16]. Moreover, Khakpour-Taleghani et al revealed that while temporary LC inactivation has no influence on the acquisition of negative experiences during avoidance learning, LC plays a role in the consolidation of this memory and converting short-term into long-term memory [17].…”
Section: Lc and Avoidance Memorymentioning
confidence: 87%
“…Similarly, according to Fan et al obtained results of an animal study, corticosterone and stress increase the expression of adrenaline-producing enzymes in LC, boost the function of the basolateral amygdala (BLA) and development of avoidance behavior [15]. Also, Shelkar et al have been reported that interaction between LC-NE and NO facilitates the expression of avoidance behavior [16]. Moreover, Khakpour-Taleghani et al revealed that while temporary LC inactivation has no influence on the acquisition of negative experiences during avoidance learning, LC plays a role in the consolidation of this memory and converting short-term into long-term memory [17].…”
Section: Lc and Avoidance Memorymentioning
confidence: 87%
“…Previous studies showed that agmatine facilitates memory retrieval in other memory tasks such as inhibitory avoidance test and MWM in healthy animals or other neurodegenerative disorders such as Alzheimer's disease. Limitations of this study for evaluating the effects of agmatine at the additional doses or number of injections are likely to be one of the causes of controversy with other studies (Dr et al, 2016;Kotagale et al, 2020).…”
Section: Discussionmentioning
confidence: 97%